Media Pop-Up Book dengan Latar Gambar Nuansa Budaya Bali untuk Meningkatkan Minat Belajar pada Topik Tata Surya - Ni Kadek Diana Yuni Pertiwi; Suranata, Kadek; Trisna, Gusti Ayu Putu Sukma (Universitas Pendidikan Ganesha, 2022)
The problem in the field is the lack of teacher innovation in developing media. It has implications for monotonous media to impact low student learning outcomes. This study aims to develop pop-up media with Balinese culture on the topic of the solar system. This type of research is the development of the ADDIE model. The research subjects were two media experts, two teachers, and three sixth-grade elementary school students. The data collection method used in this study is a questionnaire. The data analysis techniques are descriptive qualitative and quantitative analysis and inferential statistics. The study's results are the assessment of media experts, namely 4.25 (very good). The results of teacher and student responses are 5.00 (very good). The hypothesis test results are 0.000 < 0.05, so there are differences in the results of interest in learning for sixth-grade elementary school students after learning to use pop-up book media. It was concluded that the pop-up book media with Balinese cultural nuances as the background image effectively increased student interest in learning science subjects for sixth-grade elementary school students.